DOES ECO-EFFICENCY REDUCE THE COST OF EQUITY CAPITAL? EMPIRICAL EVIDENCE FROM INDONESIA - Lisa Alviani; Mahfud Sholihin (Journal of Indonesian Economy and Business (JIEB), 2015)
The objective of this study is to examine the effect of eco-efficiency on the cost of equity capital. The study hypothesizes that the implementation of eco-efficiency reduces the cost of equity capital. Using manufacturing companies listed on the Indonesian Stock Exchange for the period 2010-2012 as data, and controlling for beta, company size, Book to Market ratio, and leverage; the study finds that the implementation of eco-efficiency may reduce the cost of equity capital. The findings suggest that companies should implement ecoefficency.Keywords: cost of equity capital; eco-efficiency; ISO 14001; environmental accounting